# The function is given by the formula y = 3 (x-1) +5 (-0.2x-1) A. the value of y if x = -1. B.

**The function is given by the formula y = 3 (x-1) +5 (-0.2x-1) A. the value of y if x = -1. B. the value of the argument at which the value of the function is 2. C. the value of the argument at which the value of the function is 2 times the value of the argument.**

There is a function that is given y = 3 * (x – 1) + 5 * (-0.2x – 1). We transform by expanding the parentheses:

y = 3x – 3 – x – 5;

y = 2x – 8.

A) Find the value of the function, if x = -1, substituting the value “x” in the expression:

y = 2 * (-1) – 8 = -2 – 8 = -10.

B) Find the value “x” if y = 2:

2 = 2x – 8;

2x = 10;

x = 10/2;

x = 5.

C) If the value of the function is 2 times greater than the value of the argument, then y = 2x. Let’s equate expressions:

2x = 2x – 8;

2x – 2x = 8;

0 ≠ 8.

There are no solutions in which the value of the function is 2 times the value of the argument.